The Politics of Secular Federalism and the Federal Governance of Religious Diversity in Asia. (December 2018) - He, Baogang; Allison-Reumann, Laura; Breen, Michael
A secular approach has dominated federal studies, perhaps because there seems a natural fit between federalism and secularism. However, the federal systems or practices of Asia bring that close association into question, and the federal accommodation of religious demands has not been examined fully. This article focuses on how religion has been approached, accommodated or resisted in federal and quasi-federal states in Asia. We select India, Malaysia, Pakistan, Myanmar, Sri Lanka and Nepal as cases. We first explore the relationship between federalism, secularism and religion, and find that secular values at the point of federalisation played an important role in federalism's establishment, but that they were later modified in the practice of federal accommodation of religion. We also identify and examine the federal governance of religious diversity, which features three types of accommodation—centrally-based, unit-based and group-based accommodation—with accommodative practices sometimes being for the benefit of a majority religion, and sometimes for a minority one.